Effect of Storage Time on Nutrient Composition and Quality Parameters of Corn Silage - Betül Zehra Sarıçiçek; Birgül Yıldırım; Zahide Kocabaş; Emel Ozgumus Demir (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effects of storage duration on nutrient composition and silage quality parameters. Corn was used as silage material. Corn (31.41% dry matter) was harvested at the dough stage and fermented for 90, 104, 118, 132, 146, 160, 174, 188 and 202 days in three trench silos. The samples were brought to laboratory every 14 days. This process was repeated 9 times. After the 132th day, whereas silage crude protein (CP), ether extract (EE), ash and crude fiber (CF) contents decreased, nitrogen free extract (NFE) content increased. Lactic acid concentration of corn silage increased until the 118th day but decreased between the 118th and the 160th days. On the contrary, of decrease in LA concentration, acetic acid concentration increased depending on storage time. Ammonia nitrogen and CO2 concentration of silage increased decreased with progressing time. Storage time had significant influence on Flieg scores. The lowest score was found between days the 104th-118th. In this research, it was observed that there was a change in silage nutrient contents and fermentation characteristics with increasing storage time.